An Exploratory Study on Resilience and Interpersonal Relationships of Adults During the Work from Home in Covid-19 - Abhinandita Chakraborty; Debarati Banerjee; Mitasha Mitra; Dr. Dinaz R. Jeejeebhoy (International Journal of Indian Psychȯlogy, 2022)
Covid-19 has had a revolutionary impact on our daily life and functioning. Depression, general anxiety, irritation, and vulnerability to diseases are some of the common attributes which have been greatly impacted. Covid-19 has brought about unprecedented changes in our work culture that its effects are being studied all over the world to gain an in-depth understanding of management of these effects. The aim of this paper is to review the literature and explore the concept of working from home and the possible impact it can have on psychological attributes like resilience, loneliness and interpersonal relationships. The study tried to conduct a cross sectional research to study how these constructs vary according to age and marital status. A sample of 325 participants was collected using purposive and snowball sampling with their demographic information like age, marital status and on standardized tools of Resilience, Loneliness, and Faces-IV. Data was analyzed using t-test and one-way ANOVA to highlight differences in different levels of demographic information. ANOVA and Independent sample t-test indicated that results for Resilience, Loneliness, Communication and Satisfaction Scale of FACES IV (FACES2, FACES3) were found to be significant at 0.01 confidence level for age and marital status respectively. Conclusion: Results show that the unmarried population or the younger age group of 18-25 were found to be the most affected with deteriorated mental health, low resilience as well as high levels of loneliness. Detailed analysis, limitations and recommendations of the research were discussed.